Intersubjetividade: Necessidade Social ou Impossibilidade Cognitiva? Uma Contribuição ao Debate entre Habermas e Luhmann - Grant, Colin B. (Princípios: Revista de Filosofia (UFRN), 2010)
In this essay I set out to problematize the concepts of intersubjectivity and interaction in the theories of Germany's two foremost social philosophers: Jiirgen Habermas and Niklas Luhmann. To do so, I shall briefly reconstruct Husserl's phenomenological concept of intersubjectivity and its relationship with rational horizons and lifeworlds. I shall then demonstrate the importance of Husserl's thought in the theory of (rational) communicative action in Habermas. The third section deals with the radical rethinking of the subject (and hence intersubjectivity) in the theory of Niklas Luhmann. My principal question will then be: is it possible to reconcile critical theory with systems theory? Or, alternatively: is intersubjectivity a reality or a useful fiction?